A case study on the service quality perception in a university mall: customers' perspective. (28th July 2022) - Moohialdin, Ammar; Islam, Muhammad Saiful
This research addresses the application of an integrated approach for assessing customers' perceptions and satisfaction of services in the university mall. The case study approach was conducted by surveying the customers' response to the mall provided services. The gaps between customers' perceptions and expectations are identified by applying an integrated approach of SERVQUAL and the emotion, cognition and behaviour (E-C-B) model. This study found significant correlations between the mall environment and customers' perception of the quality metrics, including introduced products, customer arousal, customers' pleasure and purchase intention. The outcomes of this study facilitate decision making for mall and university quality managers who are engaging in improving the shopping environment as well as product and service quality. This study is also significant for researchers concerned about understanding students' expectations, satisfaction, and behaviours in university malls or similar service projects considering different environments.